Primary Melanoma of Testis- A Case Report - Pudasaini, Sujata; Joshi, Bhola Raj; Subedi, Neeraj; Pathak, Rakesh; Pande, Kricha; Koirala, Shradha; Kafle, Neeta; Bhomi, Krishna Kaji; Shahi, Aanchal (Nepalese Medical Journal, 2018)
Primary melanoma of the testis is very rare. Melanoma of testis usually occurs as metastatic tumor. Here we present a case of 54 year old man with right testicular swelling proven to be primary malignant melanoma. Patient had right scrotal swelling of six months duration. With raised LDH and unremarkable Serum β-HCG and Alpha Feto Protein level and with a suscipicion of primary testicular tumor on MRI, right inguinal orchidectomy was done. Its clinical presentation and histopathological examination is discussed here.